Resepsi Khalayak terhadap Citra Universitas Negeri Surabaya Melalui Konten Kece Media By UNESA (Jurnal Insan Pendidikan dan Sosial Humaniora, 2023)
With the increasing number of internet users, communication in educational institutions is increasing and becoming a priority. Before making a choice to one of the universities, information searches related to higher education are now also carried out. Educational institutions, especially universities, are now starting to open communication networks through social media. As Surabaya State University did, after officially holding the status of a Legal Entity University, the image of the Institution has become a priority. As of October 2022, Surabaya State University officially switched from PTN-BLU to PTN-BH through Government Regulation Number 37 of 2022, concerning State Universities with Legal Entity Surabaya State University. Therefore, there needs to be many breakthroughs in the order of public relations management in order to maintain a positive image of the Educational Institution. With a positive image of the institution, it is hoped that it will be able to increase the number of applicants, leading to an increase in university revenue. So that through the audience reception proposed by Stuart Hall in this research, it is hoped that it will be able to explain the audience's reception of the Kece Media by Unesa social media content, especially the Surabaya State University Talk program on the Unesatv Youtube channel in interpreting the messages contained in the content obtained by the audience. This research uses the Reception Analysis method using data collection techniques in the form of interviews, documentation and FGD (Focus Group Discussion). Interviews and FGDs showed that each informant gave diverse answers according to their point of view. From the interviews, it was found that the Bincang Universitas Negeri Surabaya program provides a lot of insight into what study programs are at Universitas Negeri Surabaya, what will be learned from these study programs and what graduates will become. So that audiences can find out the study program side of each Faculty at Surabaya State University. In addition, according to their views, the Bincang Universitas Negeri Surabaya program seems boring because it is presented with static viewing.